Comparison of Hybribio-H13 and Hybrid Capture® 2 human papillomavirus tests for detection of CIN2+ and CIN3+ (2024)
ABSTRACT: Introduction. Low-cost, accurate high-risk HPV tests are needed for cervical cancer screening in limited-resource settings. Objective. To compare the performance of the low-cost Hybribio-H13 test with the Hybrid Capture® 2 to detect cervical intraepithelial neoplasia grade 2 or 3 (CIN2 and CIN3). Materials and methods. Archived baseline samples tested by the Hybrid Capture® 2 from women of the ASCUS-COL trial, aged 20 to 69 years, with biopsy-colposcopy directed diagnosis of CIN2+ (n = 143), CIN3+ (n = 51), and < CIN2 (n = 632) were blindly tested by the Hybribio-H13 test. Results. The relative sensitivity of the Hybribio-H13 test versus the Hybrid Capture® 2 for detecting CIN2+ was 0.89 (90% CI = 0,80-0,98; NIT = 0,66), and for CIN3+ was 0,92 (90% CI = 0,85-0,98; NIT = 0,35). Relative specificity was 1.19 (90% CI = 1.05-1.33; NIT < 0.00001). In the analysis restricted to women older than 30 years, the relative sensitivity of the Hybribio-H13 for CIN3+ was marginally below unity (ratio = 0.97; 90% CI = 0.95-0.99), and the specificity remained higher than the Hybrid Capture® 2 test. Conclusion. The Hybribio-H13 test was as specific as the Hybrid Capture® 2 for detecting CIN2+ or CIN3+ but less sensitive. Considering these results and the young age of the population recruited for screening because of ASCUS cytology, we suggest our results warrant the evaluation of the Hybribio-H13 for screening cervical cancer, especially in the evaluated population.